Answer: See below
Step-by-step explanation:
The Pythagorean Theorem is a²+b²=c². Since each problem gives us the length of a, b, or c, we can directly plug them into this equation and solve.
Triangle EFG
9²+b²=41²
81+b²=1681
b²=1600
b=√1600
b=40
----------------------------------------------------------------------
Triangle PQR
20²+21²=c²
400+441=c²
c²=841
c=√841
c=29
----------------------------------------------------------------------
Triangle XYZ
a²+24²=25²
a²+576=625
a²=49
a=√49
a=7
Answer:
<h2>n = 8</h2>
Step-by-step explanation:
Given the nth term of an arithmetic sequence to be Tn = a+(n-1)d
a = first term of the sequence
n = number of terms
d = common difference.
Given the first element a = 2 and 22nd to be 14
T22 = a+(22-1)d = 14
a+21d = 14
Substtuting a = 2 into the equation to get d
2+21d = 14
21d = 12
d = 12/21
d = 4/7
The nth term of the sequence given a = 2 and d = 4/7 will be expressed as;
Tn = 2+(n-1)4/7
Given Tn = 6
6 = 2+(n-1)4/7
6 = 2+4/7 n - 4/7
6-2+4/7 = 4/7 n
32/7=4/7 n
32 = 4n
n = 32/4
n = 8
Start by writing what is said:
2x + 4 = -6
From there just solve for x:
Subtract 4 from both sides
2x + 4 - 4 = -6 - 4
2x = -10
Divide by 2 to get x by itself
2x/2 = -10/2
x = -5
Answer: -4/5 or -0.8
Step-by-step explanation:
m= change in y / change in x
-4/ 5